Reconstruction of the Legality Principle: The Essence of the Pancasila Spirit in Criminal Law Reform - Kartini Mallarangan (Universitas Muhammadiyah Sidoarjo, 2021)
The principle of legality is the main joint in criminal law. This is because the principle of legality relates to the rights and obligations of the community that have the potential to be subject to criminal law. This study aims to explore the values ​​of Pancasila in the renewal of the national criminal law through the reconstruction of the legality principle in the Draft Criminal Code. This research is normative legal research by prioritizing the concept and legislation approach. The results of the study confirm that the renewal of the national criminal law through the Draft Criminal Code is an important matter, especially by reconstructing the legality principle from formal legality to material legality. Reconstruction of the principle of legality is needed because the principle of legality is the heart of criminal law. This means the reconstruction of the criminal law specifically as well as the reconstruction of the principle of legality. Efforts to reconstruct the principle of legality should be guided by the values ​​of Pancasila as the ideals of Indonesian law. The reconstruction of the legality principle from formal to material, guided by the legal ideals of Pancasila is expected to be relevant to the needs and legal reality of the Indonesian people. This is so that Indonesian criminal law in the future has Indonesian ideals that it is in accordance with the nation's characteristics, personality, and legal ideals, namely Pancasila.